Strategi Komunikasi Terintegrasi Berbasis Paradigma Marketing: Upaya Museum Siwalima dalam Keterlibatan Generasi Muda - Sapulette, Angelie Natalia; Telusa, Sandra (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This article aims to analyze the integrated communication strategy grounded in marketing paradigms implemented by the Siwalima Museum to enhance youth engagement. The study is motivated by the declining interest of younger generations in cultural institutions such as museums, and the urgent need for adaptive and innovative communication approaches. Employing a qualitative methodology, this research uses a case study design, participatory observation, and in-depth interviews with museum administrators, young visitors, and strategic partners. Findings reveal that Siwalima Museum structures its communication strategy through six key stages: situational analysis, goal setting, audience targeting, message formulation, communication program development, and evaluation. These strategies manifest in thematic events, digital media utilization, creative advertising, and student-specific discount programs. The museum also applies three core marketing approaches: internal marketing through team building and staff training; integrated marketing by aligning product, price, and promotion; and relationship marketing via partnerships with schools, communities, and private sector actors through the “Friends of Siwalima Museum” initiative. The novelty of this study lies in its integration of marketing principles within public and educational museum communication, offering a holistic approach that bridges cultural values with the communication preferences of younger audiences. The study recommends that other cultural institutions adopt integrated communication strategies responsive to youth dynamics to ensure social relevance and institutional sustainability in the social sciences and humanities domain.